The Implementation of Communicative Approach Combined with Intensive Reading in Reading on the Eighth Grade Students at SMP Negeri 2 Sawan - ., Gusti Ayu Nyoman Maha Hasrini; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Dr.Sudirman, M.L.S (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini dilakukan untuk mengurangi jumlah siswa yang bermasalah dalam kompetensi membaca di kelas VIII G di SMP Negeri 2 Sawan dengan menggunakan Communicative Approach yang dikombinasikan dengan Intensive Reading. Subyek dari penelitian ini adalah 22 siswa yang terdiri dari 13 laki-laki dan 9 perempuan. Penelitian ini dalam bentuk Penelitian Tindakan Kelas (PTK). Penelitian ini dilakukan dalam dua siklus, masing-masing siklus terdiri dari empat tahapan; perencanaan, pelaksanaan, observasi, dan refleksi. Untuk mengumpulkan data, ada tiga jenis instrumen yang digunakan yaitu tes evaluasi, kuesioner, dan buku harian peneliti. Data yang didapatkan dalam penelitian ini dianalisis secara kuantitatif dan secara kualitatif. Data yang diperoleh dari tes observasi awal, dan tes evaluasi dianalisis secara kuantitatif berdasarkan kemampuan membaca siswa secara umum, kemampuan membaca siswa berdasarkan tipe teks, dan kemampuan siswa berdasarkan indikator. Sedangkan, data yang diperoleh dari kuesioner dan buku harian peneliti dianalisis secara kualitatif. Berdasarkan hasil dari kemampuan membaca siswa, ada 17 (77.28%) siswa yang bermasalah dalam membaca pada observasi awal. Di siklus I, jumlah siswa yang bermasalah dalam membaca berkurang menjadi 9 (40.91%) siswa. Setelah cycle II dilaksanakan, jumlah siswa yang bermasalah dalam membaca berkurang lagi menjadi 3 (13.63%) siswa. Sedangkan, dari jumlah siswa yang bermasalah berdasarkan tipe teks dan indikator juga berkurang secara signifikan. Dari hasil tersebut, bisa disimpulkan bahwa implementasi dari Communicative Approach yang dikombinasikan dengan Intensive Reading bisa mengurangi masalah siswa dalam membaca secara umum, tipe teks dan indikator. Kata Kunci : Communicative Approach, Membaca Intensive, Kemampuan membaca. This study was conducted in order to decrease the number of students that had problem in reading competency in VIII G class of SMP Negeri 2 Sawan by using Communicative Approach Combined with Intensive Reading. The subject of the study were 22 students consisting of 13 males and 9 females. The study was designed in the form of classroom action research. It was conducted in two cycles, each cycle consisted of four steps; planning, action, observation, and reflection. To collect the data, there were three kinds of instruments used namely evaluation test, questionnaire, and researcherâs diary. The data obtained in this study were analyzed quantitatively and qualitatively. The data gained from preliminary observation test and evaluation test were analyzed quantitatively based on studentsâ general reading competency, studentsâ reading competency based on text types, and studentsâ reading competency based on indicators. Meanwhile, the data gained from questionnaire and researcherâs diary were analyzed qualitatively. Based on the result of studentsâ reading competency, there were 17 (77.28%) students that had problem in reading in preliminary observation. In cyle I, the number of students who had problem in reading decreased into 9 (40.91%) students. After cycle II had been conducted, the number of students that had problem in reading decreased again into 3 (13.63%) students. Meanwhile, from the number of students who had problem based on the text types and indicators were also decreased significantly. From the result, it could be concluded that the implementation of Communicative Approach combined with Intensive Reading was able to decrease the studentsâ problem in general reading competency, text types, and indicators. keyword : Communicative Approach, Intensive Reading, Reading Competency.